La población desplazada en Colombia: ¿Hacia un nuevo estado de cosas inconstitucionales? - Higuera Jiménez, Diego Mauricio (Corporación Universitaria Americana, 2018)
The present work leads us to a broad reflection on the most vulnerable populations that afflict Colombian society; that is why today we dedicate this research to them in order to debate and question the actions of state authorities regarding the fulfillment of fundamental rights that so far have remained in a perpetual constitutional transgression, which has led to the declarations of unconstitutional states of affairs -ECI- and yet these have not been sufficient for the satisfaction and solution of their problems. It is with the above that we refer to the name of this book, because from the evident non-compliance of the structural failures generated from the declaration of an ECI, we postulate the importance of restructuring it with new measures, proposing the new unconstitutional state of affairs -NECI- and thus ending the prolonged transgression that has been occurring on a massive scale against fundamental rights.